A 2.5-5 μm spectroscopic study of hard X-ray selected AGNs with AKARI. Issue Volume 9:Issue S304(2013) (25th July 2014) - Castro, A.; Miyaji, T.; Shirahata, M.; Oyabu, S.; Clark, D.; Ichikawa, K.; Imanishi, M.; Nakagawa, T.; Ueda, Y.
Abstract: We explore the relationships between the 3.3 μm polycyclic aromatic hydrocarbon (PAH) feature and active galactic nucleus (AGN) properties of a sample of 54 hard X-ray selected bright AGNs, including both Seyfert 1 and Seyfert 2 type objects, using the InfraRed Camera (IRC) on board the infrared astronomical satellite AKARI . The sample is selected from the 9-month Swift /BAT survey in the 14-195 keV band and all of them have measured X-ray spectra at E ≲ 10 keV. These X-ray spectra provide measurements of the neutral hydrogen column density ( N H ) towards the AGNs. We use the 3.3 μm PAH luminosity ( L 3.3μm ) as a proxy for star formation activity and hard X-ray luminosity ( L 14-195keV ) as an indicator of the AGN activity. We searched for possible difference of star-formation activity between type 1 (un-absorbed) and type 2 (absorbed) AGNs. Our regression analysis of log L 14-195keV versus log L 3.3μm shows a positive correlation and the slope seems steeper for type 1/unobscured AGNs than that of type 2/obscured AGNs. The same trend has been found for the log ( L 14-195keV / M BH ) versus log ( L 3.3μm /MBH ) correlation. Our analysis show that the circum-nuclear star-formation is more enhanced in type 2/absorbed AGNs than type 1/un-absorbed AGNs for low X-ray luminosity/low Eddington ratio AGNs.